The effect of auditor attributes on perceived audit quality: evidence from Jordan - Alsmairat, Yazan Yaseen Yousef (School of Business Innovation & Technopreneurship, 2018)
This study focuses on the four main audit attributes: audit tenure, audit firm size, the level of compliance toward ethics rules and the reliance on internal audit work to audit quality in Jordan. Furthermore, data for this study collected from Jordanian auditors by distributing questionnaire. From the total population of registered Jordanian auditors are 419 auditors, attached in Appendix A. The actual sample for this study 200 auditors in Jordan.